2022
DOI: 10.1108/rpj-02-2022-0064
|View full text |Cite
|
Sign up to set email alerts
|

Lightweight design of an AlSi10Mg aviation control stick additively manufactured by laser powder bed fusion

Abstract: Purpose This paper aims to explore a structural optimization method to achieve the lightweight design of an aviation control stick part manufactured by laser powder bed fusion (LPBF) additive manufacturing (AM). The utilization of LPBF for the fabrication of the part provides great freedom to its structure optimization, further reduces its weight and improves its portability. Design/methodology/approach The stress distribution of the model was analyzed by finite element analysis. The material distribution pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 29 publications
(31 reference statements)
0
3
0
Order By: Relevance
“…In the case of high energy input, distortions and irregularities will appear because of big melt pool volumes and recoil pressure aspects. It was found that the stability of the melt pool is a significant factor in producing high-density components (Kempen et al , 2012; Kempen et al , 2015; Wang et al , 2022).…”
Section: Characteristics Of Produced Componentsmentioning
confidence: 99%
“…In the case of high energy input, distortions and irregularities will appear because of big melt pool volumes and recoil pressure aspects. It was found that the stability of the melt pool is a significant factor in producing high-density components (Kempen et al , 2012; Kempen et al , 2015; Wang et al , 2022).…”
Section: Characteristics Of Produced Componentsmentioning
confidence: 99%
“…Furthermore, in respect of metal manufacturing, PBF is increasingly being employed due to its high degree of fabrication freedom without the use of other part-specific supplies, short design and fabrication periods, and the revolution of conventional manufacturing technologies in realizing an immense amount of time saved and low commercial costs [6][7][8]. In short, not only does PBF manufacturing not require extra devices, but it is also not restricted by complex part geometry, giving rise to multitudinous advantages, such as speediness, a short production period, and low cost [9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…The optimization results were used as the basis for size optimization to determine the optimal combination of structural parameters and further realize the lightweight design of temporary rectangular shield support device. 16,17 According to different roadway handling and disassembly requirements, the modular lightweight matching research is carried out for modules with large volume and mass ratios, and optimal matching scheme is determined. Finally, the finite element software was used to simulate and analyze the key modules to verify the reliability of the lightweight design.…”
Section: Introductionmentioning
confidence: 99%